Organo-montmorillonite as an electrical treeing retardant for polymeric insulating materials - Jamil, A.A.A. (2012)
This paper presents investigation on the propagation of electrical treeing in silicone rubber samples filled with Montmorillonite (MMT) and Organo-montmorillonite (OMMT) nanoclays as fillers for electrical tree inihibition. Treeing experiments were conducted by applying ac voltage with increasing rate of 0.5 kV per second at power frequency on pure silicone rubber, silicone rubber filled with 1% MMT and silicone rubber filled with 1% OMMT samples respectively and treeing propagation length and inception voltage within 30 minutes aging period were observed. Result from this study showed that the silicone rubber/OMMT sample exhibited the shortest tree length as well as highest tree inception voltage followed by the silicone/MMT sample with the pure silicone rubber having the least electrical performance. This finding suggests the OMMT can be used a filler in polymeric insulating materials for electrical tree inhibition.